The influence of hormonal replacement therapy on alveolar ridge bone in perimenopuasal women - Bakalczuk, Magdalena; Bakalczuk, Szymon; Różyło, Teresa Katarzyna; Kleinrok, Janusz (Menopause Review/Przegląd Menopauzalny, 2006)
Objectives and study design: Finding relationships between taking HRT and the state of alveolar process as research work connected with evaluation of oral cavity and prosthetic base in population of women in perimenopausal age. Materials and methods: For the purpose of this study there were qualified 82 peri- and postmenopuasal women with mean age 50 years (standard deviation ±4.69). The women were divided into 3 groups in regard to the presence of menstruation and HRT, as follows: group 1 – women menstruating without HRT; group 2 women non-menstruating without HRT; group 3 – menstruating and non-menstruating women taking HRT. Further analysis was carried out separately within each group. Forearm bone mineral density was measured by means of the SXA method (single X-ray absorptiometry) Basing on the radiographs, mean alveolar bone density was calculated after measurements of five regions of interest placed in premolars area, both mandible and maxilla. The results were used in order examine relationships between forearm bone mineral density as well as hormone blood serum level, with regard to both FSH and E2, and the results of alveolar process bone density measurement. Results: No significant, strong correlations were found (r>0.4 and p>0.05). Statistical analysis brought in results only strong significant negative linear correlation (r=-0.63, p<0.005) between FSH level and mandibular alveolar bone density. In the group of menstruating and non-HRT women (group 1) as well as in the group of non-menstruating women without HRT (group 2) weak relationship (r=0.36 and p<0.04) between ulna BMD and maxillary alveolar bone density was determined. There were not observed correlation between hormone blood level as well as forearm BMD and alveolar bone density in the group of women taking HRT. Conclusions: Studies on linear correlation between influence of taking HRT and alveolar process density showed that taking HRT during and after menopause did not have influence on state of the alveolus. Taking E/HRT may stop the loss of alveolar bone and decreases number of preparing problems with dentures in future.